The Lattice Structure and Optical Properties of Neodymium-Doped Gadolinium Vanadate Crystals Induced by Ion Irradiation - Mei Qiao; Tiejun Wang; Honglian Song; Jing Zhang; Yong Liu; Peng Liu; Huaijin Zhang; Xuelin Wang (IEEE Photonics Journal)
In recent times, the neodymium-doped gadolinium vanadate (Nd:GdVO4) crystal has attracted significant attention as one of the most valuable functional materials, but its lattice structure can be easily modified in an irradiation environment, which determines its related optical properties and affects the performance of devices based on the Nd:GdVO4 crystal. The near-surface lattice structure change and damage are studied through the displacement per atom (dpa), X-Ray diffraction, hardness and elastic (Young's) modulus, and micro-Raman spectroscopy techniques. We discover that the intensity and peak position of micro-Raman have obvious changes between waveguide and substrate region in Nd:GdVO4 crystal. The related optical properties induced by the structural changes, including the absorption bands and refractive index profiles, are investigated. A new absorption peak was observed after irradiation of the Nd:GdVO4 crystals by C3+ ions. Thus, waveguide optical-coupling techniques identified that the ion- irradiated Nd:GdVO4 crystal can support single-mode or multimode propagation at 633 nm. The fabricated waveguide structures emerge as promising candidate for photonic design and integrated optical devices, which will have a huge application prospect in multimedia and internet.